Current state of prostate cancer treatment and future strategies - Yeonhee Pyo; Ki Han Kwon (Journal of Men's Health)
Prostate cancer (PCa) is the most common malignancy in men. It forms heterogeneous PCa masses with lining epithelial cells that require androgen signaling, and heterogeneous PCa masses can metastasize to lymph nodes and bone, making early diagnosis and treatment critical. PCa treatments include chemical castration, surgical resection, chemotherapy, hormonal changes, and androgen deprivation therapy. Diagnosis begins with a digital rectal exam (DRE) or prostate-specific antigen, and is often associated with a negative prognosis and pain. Furthermore, malignancy metastasizes or recurs to the bone. It is vital to develop personalized treatment based on the understanding of cancer pathophysiology. PCa is an aggressive multifactorial disease being focused in men’s health research. PCa handling is crucial in men’s survival. It is constantly studied for diagnosis, prevention and treatment. This article reviews it from therapeutic perspective. It thus summarizes current and emerging therapeutic strategies and biomarkers for PCa.